2011
DOI: 10.1371/journal.pone.0019549
|View full text |Cite
|
Sign up to set email alerts
|

Specific Impact of Tobamovirus Infection on the Arabidopsis Small RNA Profile

Abstract: Tobamoviruses encode a silencing suppressor that binds small RNA (sRNA) duplexes in vitro and supposedly in vivo to counteract antiviral silencing. Here, we used sRNA deep-sequencing combined with transcriptome profiling to determine the global impact of tobamovirus infection on Arabidopsis sRNAs and their mRNA targets. We found that infection of Arabidopsis plants with Oilseed rape mosaic tobamovirus causes a global size-specific enrichment of miRNAs, ta-siRNAs, and other phased siRNAs. The observed patterns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
1
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 84 publications
3
46
1
2
Order By: Relevance
“…S2) was only moderately induced and CDC48C (At5g03340) transcript levels remained largely constant at both time points. The virus-induced induction of CDC48B is in agreement with our independent microarray analysis of transcript levels upon ORMV infection (Hu et al, 2011;Supplemental Table S2) and other publicly available microarray data describing CDC48 transcript levels in the presence of different environmental stresses (https://www.genevestigator. com/gv/index.jsp and http://www.weigelworld.org/ resources/microarray/AtGenExpress/), indicating that CDC48B represents the main stress-responsive CDC48 isoform in Arabidopsis.…”
Section: Virus Infection Induces Expression Of Cdc48b In Arabidopsissupporting
confidence: 89%
See 2 more Smart Citations
“…S2) was only moderately induced and CDC48C (At5g03340) transcript levels remained largely constant at both time points. The virus-induced induction of CDC48B is in agreement with our independent microarray analysis of transcript levels upon ORMV infection (Hu et al, 2011;Supplemental Table S2) and other publicly available microarray data describing CDC48 transcript levels in the presence of different environmental stresses (https://www.genevestigator. com/gv/index.jsp and http://www.weigelworld.org/ resources/microarray/AtGenExpress/), indicating that CDC48B represents the main stress-responsive CDC48 isoform in Arabidopsis.…”
Section: Virus Infection Induces Expression Of Cdc48b In Arabidopsissupporting
confidence: 89%
“…Comparison of expression levels of ER stress-responsive chaperones, lectins, and transcription factors in biologically independent Arabidopsis transcriptome data of ORMV-infected and mock-inoculated plants (Hu et al, 2011) further validated this finding (Supplemental Table S2) and thus indicated the induction of ER stress and enhanced protein quality surveillance in virusinfected tissues. The observed induction of CDC48B Figure 1.…”
Section: Cdc48b Functions In Er Maintenance Upon Er Stressmentioning
confidence: 58%
See 1 more Smart Citation
“…SOAP denovo-Trans tool has been reported to be effective in de novo transcriptome assembly (Xie et al 2014). Transcriptome sequencing has been successfully applied in characterising many viruses (Deboever et al 2013;Hu et al 2011;Barba et al 2014;Massart et al 2014). This can primarily be used to approve the complete virus elimination status.…”
Section: Discussionmentioning
confidence: 99%
“…Infection of Arabidopsis plants with Oilseed rape mosaic virus (Tobamovirus) causes a global sizespecific enrichment of micro RNAs (miRNAs) and other phased siRNAs. The observed patterns of sRNA enrichment suggest that in addition to a role of the viral silencing suppressor, the stabilization of sRNAs might also occur through association with unknown host effector complexes induced upon infection [18]. Small RNA analysis by Illumina sequencing from a non-coding region of Cauliflower mosaic virus (CaMV) in Arabidopsis indicated the mechanism of CaMV small RNAs as decoy RNAs to evade silencing machinery from viral promoter and coding regions [6].…”
Section: Study Of Antiviral Defence Mechanismmentioning
confidence: 99%